Análisis comparativo del uso de herramientas educativas virtuales manejadas por los docentes y alumnos en la UTB y UTPL del Ecuador - Gutiérrez Reyes, Natali Victoria (2021)
This paper shows an investigation of the comparative analysis of the use of educational tools by teachers of UTB and UTPL in Ecuador. Educational platforms are those that offer a wide range of functions, intended for the use of both higher education institutions and educational units. Currently these educational platforms are playing a very important role, due to the pandemic, MOODLE and CANVASUTPL were analyzed and compared. The research that was carried out is of documentary type, because the documentation of the two platforms was done, and a commentary was issued based on the research that was done, collecting, studying and analyzing, the information obtained from different articles, computer magazines, etc.. As a result of both platforms mentioned above, both have the most basic that an LMS platform should have, with some tools that add a plus. . A comparative analysis was made between the "Canvas" and "Moodle" platforms and it was deduced that both contain the basic characteristics that LSM platforms should have, designed to provide teachers and students with a robust and secure system, with the difference that Moodle is a platform with easy-to-manipulate properties and is continuously revised and improved, which facilitates its use for administrators, teachers and students.